Chemical composition and antibacterial properties of Curcuma aeruginosa Roxb. essential oil against acne-related bacteria - Mulyaningsih, Sri; Millah, Azzahro Imada; Darmawan, Endang (Pharmaciana, 2025)
Curcuma aeruginosa Roxb. is used empirically for various treatments, including maintaining healthy skin. However, adequate research is needed before use for medicinal purposes. This study was proposed to determine the chemical content and antibacterial properties of C. aeruginosa against acne-causing bacteria. Water-steam distillation was applied to distill the essential oil. Its organoleptic, yield, and refractive index were also determined. Gas chromatography-mass spectrometry (GC-MS) was performed to identify the chemical compounds. The antibacterial property against acne-causing bacteria was investigated using the diffusion and microbroth dilution methods. The essential oil of C. aeruginosa had a bitter taste, an aromatic odor, and a brownish color with a yield of 0.66% and a refractive index of 1.4921. GC-MS analysis showed 1,8-cineole (30.72%) as the major compound. The inhibition zone diameter varied based on the test bacteria. The 10% essential oil was better at inhibiting Propionibacterium acnes than Staphylococcus aureus or Staphylococcus epidermidis. The MIC and MBC values of the essential oil against P. acnes were the same at 0.07%. The C. aeruginosa essential oil has the potential to be developed into anti-acne preparations.